Penerapan Program Linear Metode Simpleks untuk Memaksimalkan Keuntungan pada Penjualan UMKM - Nerli Khairani; Asni Al Amini; Mhd Fachrizal; Adinda Saputri; Livia Mutianda (Pusat riset dan Inovasi Nasional, 2026)
Micro, Small, and Medium Enterprises (MSMEs) often face challenges in managing production resources, such as limited raw materials and labor time, resulting in suboptimal business profits. This study aims to determine the production combination that can generate maximum profits for culinary MSMEs producing risol and pastel using the simplex linear programming method. The study employed a quantitative descriptive method with a case study approach. Data were obtained through interviews, observations, and documentation of the MSME's daily production activities. The data used included wheat flour raw material usage, production time, output quantity, and profit for each product. The results showed that the optimal production combination was achieved when producing 2.5 risol recipes and 0.5 pastel recipes, with a maximum profit of IDR 252.375 per day. These results demonstrate that the application of the simplex method can help MSMEs optimize the use of production resources more effectively and efficiently, thereby increasing business profits.